Examining negative emotional states, daytime drowsiness & resting-state cognition on resting-state EEG patterns & sleep quality in young & older adults - Ho, Jonas Chan Wai (2024)
As individuals age, sleep quality is reported to decrease compared to earlier stages of life. these declines often coincide with an increase in the incidences of poor health outcomes, including physiological, psychological and neurodegenerative disorders. given the critical link between sleep quality and health in ageing, addressing sleep concerns may be vital to encourage healthier ageing. however, it is important to recognise the reciprocal relationship between these factors. poor lifestyle factors and illness can create sleep disturbances, while poor sleep quality may also exacerbate health conditions. therefore, it is vital to consider whether poor sleep quality necessarily worsens with age, which may serve as a catalyst for age-related pathologies, or if the onset of such pathologies may exacerbate sleep disturbances, leading to a cycle of declining health and sleep quality.